The attitudes of ESL teachers in Sabah towards technology integration - Ahmad Abdul Rauf; Suyansah Swanto (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
Technology integration in teaching and learning activities has become one of the debatable issues among educators in recent years. This is due to the fact that countries all over the world have injected millions of dollars to integrate technologies in education. Malaysia, being one of the developing countries, has also devised many plans and programs to integrate related technological tools and materials in schools. For that, this study examined English as a Second Language (ESL) teachers’ attitudes towards the use of technology in the teaching of English at secondary schools in Sabah. This is essential to assist in developing any future programs or trainings by the relevant authorities. The study applied quantitative method and used cluster sampling to choose participants which comprised 100 of ESL secondary school teachers in Sabah. Findings of the study disclosed that ESL teachers have positive beliefs and attitudes toward the technology integration.